1971
DOI: 10.1042/bj1230959
|View full text |Cite
|
Sign up to set email alerts
|

The role of cholesteryl 14-methylhexadecanoate in peptide elongation reactions

Abstract: 1. Peptide-elongation factors were purified from rat liver and hurnan tonsils and the contents of cholesteryl 14-methylhexadecanoate were determined in fractions obtained during enzyme purification. The relative contents of this compound in purified enzyme preparations was several times higher than that in the crude starting material. Elongation factors from human tonsils contained a significantly larger quantity of the cholesteryl ester than enzytne from rat liver. 2. Transfer enzymes extracted with various o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
43
0

Year Published

1971
1971
1989
1989

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 23 publications
9
43
0
Order By: Relevance
“…Hradec and coworkers (13) first reported that EF-1 preparations contained a unique cholesterol ester (cholesterol-14-methylhexadecanoate) which was also present in a complex of aminoacyl-tRNA synthetases (14). A similar result on the presence of cholesterol in a eukaryote aminoacyl-tRNA synthetase preparation has been reported by Bandyopadhyay and Deutscher (16).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Hradec and coworkers (13) first reported that EF-1 preparations contained a unique cholesterol ester (cholesterol-14-methylhexadecanoate) which was also present in a complex of aminoacyl-tRNA synthetases (14). A similar result on the presence of cholesterol in a eukaryote aminoacyl-tRNA synthetase preparation has been reported by Bandyopadhyay and Deutscher (16).…”
Section: Discussionsupporting
confidence: 54%
“…Cholesterol-14 methylhexadecanoate was not found in the EF-1 preparations from calf brain, and preliminary attempts on our -part to activate EF-1H preparations that have been extracted with organic solvents as described by Hradec et al. (13) have been unsuccessful. We do not know whether EF-1H merely represents a storage form of EF-1L, a high-molecular-weight regulatory complex, or an artifact of the isolation procedure.…”
Section: Discussionmentioning
confidence: 97%
“…Blood was withdrawn by cardiac puncture into bottles containing a solution of heparin (50 units/ml of blood) and was chilled immediately in ice. Polyribosomes from rat liver were isolated as described by Hradec et al (1971) and ribosomal subunits from rat liver as reported by Hradec et al (1974). Peptide-elongation factors were separated and purified by the method of Bermek & Matthaei (1970).…”
Section: Animalsmentioning
confidence: 99%
“…Assay of radioactivity Portions of incubation mixtures (75,u1) in which peptide-bond formation was assayed were applied to discs of Whatman GF 83 filters, and the filters were washed as described by Hradec et al (1971). Mixtures for the assay of aminoacyl-tRNA formation were treated in the same way, omitting only washing with hot trichloroacetic acid.…”
Section: Incubationsmentioning
confidence: 99%
“…This stimulating effect on enzymes present in the soluble fraction of the cell has been investigated in our laboratory during the past years [2,31. Evidence has been obtained that the presence of this compound in the molecules of aminoacyl-tRNA synthetases [4] as well as in peptide elongation factors [5] may be essential for the normal activity of these enzymes.…”
Section: Introductionmentioning
confidence: 99%